Die Problematik des Begriffes hebraica veritas - Loader, James Alfred (HTS teologiese studies, 2008)
The formal problematic of the concept hebraica veritas Proceeding from the importance of the concept of hebraica veritas in terms of both its original intention and of the opposing positions on Holy Scripture entertained by the Roman Catholic tradition and the emerging Protestant views during the Reformation, a brief discussion of the meaning and early context of the concept is given. The formal problematic of the hebraica veritas as found in the Tanak is addressed vis-à-vis its latinised version in the Greek text tradition. Jerome’s use of the concept is analysed on the basis of his textual justification for it. Pneumatological and salvation-historical dimensions are identified, and the function of the concept as self-identification over against Judaism is discussed, as well as its implications for delimiting the canon. It is concluded that the concept needs to be foregrounded anew in light of its significant impact in the context of accounting for the concepts of Holy Scripture, canon and therefore canon-based endeavours to construe a “biblical theology” of the “whole Bible”.